Surgical treatment of AO/OTA 41B3 and 41C tibial plateau fractures with a temporary bi-frame fixator combined with the MIPPO technique - Xu-Song Li; Jun-Le Wu; Lin Ye; Li-Ben Huang; Jie-Feng Huang (BMC Musculoskeletal Disorders)
Abstract Background This study evaluated the clinical effects of the use of a temporary bi-frame fixator in conjunction with minimally invasive percutaneous plate osteosynthesis (MIPPO) for treating AO/OTA 41B3 and 41C tibial plateau fractures (TPFs). Methods This was a retrospective analysis of 30 patients with TPFs affected by vertical compression seen from October 2019 to October 2020. All patients were treated with a bi-frame fixator to correct the vertical shortening deformity, with the MIPPO technique used after reduction. All patients underwent routine examinations at 1, 3, 6, 12 and 24months postoperatively and then annually. Clinical parameters assessed included the Hospital for Special Surgery score (HSS), number of assistants, intraoperative hemorrhage, intraoperative fluoroscopy frequency, length of hospital stay, and time to fracture healing. Radiographic findings were assessed using Rasmussen scores. Results All patients had satisfactory fracture reduction on postoperative imaging. The average operating time was 112.03 ± 20.9 min, with 15.79 ± 3.45 fluoroscopic exposures; the average blood loss was 66.63 ± 10.88 mL, the average length of hospital stay was 12.86 ± 5.11 days, and the average fracture healing time was 10.33 ± 1.48 weeks. The mean follow-up time was 23.18 ± 2.59 months. At the last follow-up, the Rasmussen anatomical score was excellent in 22 (75.3%) patients, good in 5 (16.7%), and fair in 3 (10%). The average HSS was 65.7 ± 3.26, 82.26 ± 2.28, and 87.66 ± 2.4 after 1, 6, and 12 months, respectively, and it was 92.56 ± 2.96 at the last follow-up (F = 1073.073, P < 0.001). No complications occurred in any patient during follow-up. Conclusion For AO/OTA 41B3 and 41C fractures of the tibial plateau, the use of a temporary bi-frame fixator combined with the MIPPO technique can correct the compressed displacement, reduce soft tissue damage, and facilitate surgical reduction, which aid the recovery of joint function.